Statin-Induced Myopathy - D. A. Sychev; T. M. Ostroumova; O. D. Ostroumova; A. I. Kochetkov; S. V. Batyukina; E. V. Mironova (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2023)
Scientific relevance. Being the main class of medicinal products for dyslipidaemia treatment, statins are widely used in clinical practice in various patient populations. However, statins can cause statin-associated muscle symptoms (SAMS), which are the most frequent and, in some cases, even life-threatening adverse reactions associated with these medicinal products.Aim. The study aimed to perform a systematic review of the epidemiology, classification, and physiological pathogenesis of SAMS, risk factors for this complication, and clinical guidelines for primary care physicians regarding the identification and treatment of patients with SAMS.Discussion. SAMS is an umbrella term that covers various forms of myopathies associated with satin therapy. According to the published literature, the prevalence of SAMS varies considerably and may depend on the study design, inclusion criteria, and the medicinal product used. SAMS has multiple putative pathogenic pathways that include genetically determined processes, abnormalities in mitochondrial function, defects in intracellular signalling and metabolic pathways, and immune-mediated reactions. The main known risk factors for developing SAMS include high-dose statins, drug-drug interactions, genetic polymorphisms, female sex, older age, Asian race, history of kidney, liver, and muscle disease, and strenuous physical activity. Given the lack of universally recognised algorithms for diagnosing SAMS, clinicians should consider the clinical presentation and the temporal relationship between statin therapy and symptoms. Other factors to consider include changes in muscle-specific enzyme levels and, in some cases, the results of blood tests for antibodies to 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase.Conclusions. To ensure the safety of statin therapy, it is essential to raise clinicians' awareness of the risk factors for SAMS, indicative clinical and laboratory findings, and the need for dynamic patient monitoring, including the involvement of clinical pharmacologists.